The NAFLD‐MAFLD debate: Eminence vs evidence. (2nd December 2020) - Fouad, Yasser; Elwakil, Reda; Elsahhar, Medhat; Said, Ebada; Bazeed, Shamardan; Ali Gomaa, Ahmed; Hashim, Almoutaz; Kamal, Enas; Mehrez, Mai; Attia, Dina
Abstract: Debates are inevitable in science and could be a powerful tool for addressing controversial topics as it promotes critical thinking and inspires individuals to consider alternate viewpoints. However, debates can help only to identify the issues that need to be clarified to address this question, but it can never help resolve the controversy itself. In the era of evidence‐based medicine, the need for an evidence‐based debate is mandatory. Polarising opinions and major debate have recently arisen in hepatology on the nomenclature and diagnostic criteria for fatty liver disease associated with metabolic dysfunction (non alcoholic fatty liver disease [NAFLD]‐metabolic (dysfunction) associated fatty liver disease [MAFLD] debate). The aim of this viewpoint is to suggest a way to settle the debate through evidence. Descriptive review using PubMed to identify literature on the evidence and eminence‐based medicine and studies comparing MAFLD and NAFLD criteria. The emerging studies comparing the performance of diagnostic criteria of NAFLD and MAFLD represent the dawn of a new era for reframing the ongoing debate by acquisition of the mandatory evidence that will both resolve the debate and lead to novel avenues of research. In conclusion, the time has come to hold debate and focus on gathering and building the evidence to settle it. It does not matter who wins the debate and once there is robust evidence, we should all follow it wherever it leads.